(untitled) - Vakil, C. N. (New York, 1937)
Tells us about ommercial relations between India and Japan
Keywords: Cotton trade,India,Buôn bán vải sợi,Japan,Ấn Độ,Nhật bản; Commerce,Commerce,Thương mại,Thương mại; Japan,India,Nhật Bản,Ấn Độ